2021
DOI: 10.3390/cli9100145
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Climate Variability on Maize Production in the Ejura-Sekyedumase Municipality, Ghana

Abstract: Agriculture is one of the sectors most susceptible to changes in climatic conditions. The impact is even stronger in Africa, where rain-fed agriculture is vital for daily subsistence, but where adaptive capacity is low. It is therefore crucial to increase the understanding of the actual climate change dynamics on agricultural productivity. This study examined the effects of changes in climatic variables such as rainfall and temperature on maize production in the Ejura-Sekyedumase Municipality, Ghana. Regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…The presence of higher rainfall during 2019 cropping year may have been conducive to achieve improved grain yield. Consistent with this result, Cudjoe et al [ 35 ] reported a positive relationship between annual rainfall and maize yield. The results also revealed that grain yield of maize intercropped with 25% of faba bean density (5.56 t ha −1 ) surpassed the grain yield of maize intercropped with 75% faba bean density by about 18.5% ( Table 1 ).…”
Section: Resultssupporting
confidence: 67%
“…The presence of higher rainfall during 2019 cropping year may have been conducive to achieve improved grain yield. Consistent with this result, Cudjoe et al [ 35 ] reported a positive relationship between annual rainfall and maize yield. The results also revealed that grain yield of maize intercropped with 25% of faba bean density (5.56 t ha −1 ) surpassed the grain yield of maize intercropped with 75% faba bean density by about 18.5% ( Table 1 ).…”
Section: Resultssupporting
confidence: 67%
“…This is because the category of people was aware to this statement that rainfall pattern causes poor yield and the maize will failure. This implies that the majority of the respondents were strongly agree with the statement so that This findings are supporting Cudjoe, Antwi-Agyei, and Gyampoh, (2021) [17], provided strong evidence about rainfall pattern and maize production.…”
Section: Effect Of Rainfall Pattern On Maize Productionsupporting
confidence: 75%
“…Sample is a further subset of the target population which we would like to include in the study. Thus a sample is a portion, piece, or segment that is representative of a whole [17]. The sample size of the study was 108 farmer.…”
Section: Sample Sizementioning
confidence: 99%
“…It is noteworthy that farmers in the Ejura Sekyeduamse District are leading producers of maize, beans and peanuts in Ghana. 20 When cereals are contaminated with aflatoxins, some of the suggested harmful effects on humans are vomiting, diarrhea, hepatitis, cirrhosis, immunosuppression, miscarriages, mutagenic and teratogenic effects, and different cancers. 21 One of the most fundamental approaches to lowering the risk of aflatoxicosis in humans is to avoid eating foods contaminated with aflatoxin.…”
Section: Discussionmentioning
confidence: 99%